Localization of type IV membrane during collagen alpha 1 to alpha 6 chains in basement mouse molar germ development - Nagai, N.; Nakano, K.; Sado, Y.; Naito, I.; Gunduz, M.; Tsujigiwa, H.; Nagatsuka, H.; Ninomiya, Y.; Siar, C.H. (2001)
The dental basement membrane (BM) putatively mediates epithelial-mesenchymal interactions during tooth morphogenesis and cytodifferentiation. Type IV collagen a chains, a major network-forming protein of the dental BM, was studied and results disclosed distinct expression patterns at different stages of mouse molar germ development. At the dental placode and bud stage, the BM of the oral epithelium expressed alpha1, alpha2, alpha5 and alpha6 chains while the gubernaculum dentis, in addition to the above four chains, also expressed alpha4 chain. An asymmetrical expression for alpha4, alpha5 and alpha6 chains was observed at the bud stage. At the early bell stage, the BM associated with the inner enamel epithelium (IEE) of molar germ expressed alpha1, alpha2 and alpha4 chains while the BM of the outer enamel epithelium (OEE) expressed only alpha1 and alpha2 chains. With the onset of dentinogenesis, the collagen alpha chain profile of the IEE BM gradually disappeared. However from the early to late bell stage, the gubernaculum dentis consistently expressed alpha1, alpha2, alpha5 and alpha6 chains resembling fetal oral mucosa. These findings suggest that stage- and position-specific distribution of type IV collagen alpha subunits occur during molar germ development and that these changes are essential for molar morphogenesis and cytodifferentiation.